2016
DOI: 10.1186/s13048-016-0269-0
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA in the hu man ovarian follicular fluid acts as an antioxidant factor on granulosa cells

Abstract: BackgroundA previous study showed that dopamine (DA), which is contained in follicular fluid (FF) from IVF patients, strongly increased the production of reactive oxygen species (ROS) by cultured human granulosa cells (GCs). ROS, including H2O2, are assumed to play roles in ovarian physiology and pathology. Ovarian DA could be derived from the circulation, ovarian innervation and/or unknown ovarian sources. L-DOPA is the direct precursor of DA in its synthetic pathway. It was not yet described in FF. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Less production of amines may further lead to a decrease in epinephrine synthesis and consequently a reduced D2R expression. Blohberger et al detected DDC expression in theca cells of the ovary and assume a correlation between DDC expression and higher dopamine levels within the ovary ( 6 ). Generation of dopamine from L-DOPA is the standard treatment for Parkinson’s disease ( 20 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less production of amines may further lead to a decrease in epinephrine synthesis and consequently a reduced D2R expression. Blohberger et al detected DDC expression in theca cells of the ovary and assume a correlation between DDC expression and higher dopamine levels within the ovary ( 6 ). Generation of dopamine from L-DOPA is the standard treatment for Parkinson’s disease ( 20 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme l -dopa-decarboxylase (aromatic amino acid decarboxylase, DDC), which is expressed by the placenta, is responsible for the conversion of l -dopa into dopamine ( 5 , 6 ). Additionally, DDC is involved in the synthesis of serotonin, tryptamine, phenylethylamine and histamine ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…When L-dopa is decarboxylated to dopamine (DA) by aromatic L-amino acid decarboxylase (AADC), ROS are generated that could ultimately lead to cell death [47]. Nevertheless, L-dopa in some in vivo and in vitro experiments had no toxic effects, or even showed antioxidant capabilities [48][49][50][51]. Oxidative stress in peripheral blood mononuclear cells from patients with PD is negatively correlated with L-dopa dosage [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the perinatal 6-OHDA lifelong model of PD, elevated basal levels of ROS occurring in denervated dopaminergic striatum are suppressed by L-dopa treatment [50]. L-Dopa in follicular fluid is an antioxidant factor and exerts positive influences on cultured human granulosa cells, whereas DA derived from L-dopa has opposite actions [51]. In the present work, we have found that L-dopa corrects 6-OHDA-induced decrease of 5-HT 2B receptor in astrocytes in primary cultures, suggesting L-dopa that may protect cells by its antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme oxidative stress is able to induce granulosa cell apoptosis (57); however, the antioxidant factor would exert a positive effect. L-DOPA in FF as an antioxidant factor that exerts positive influences on granular cells, including decreasing H 2 O 2 production and promoting cell survival (58). Based on these observations, AOPPs may decrease P 4 production via impairing the function of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%